2010
DOI: 10.1007/s11259-010-9421-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma pharmacokinetics and milk levels of ceftriaxone following single intravenous administration in healthy and endometritic cows

Abstract: Pharmacokinetics and milk levels of ceftriaxone were studied in healthy and endometritic cows following single intravenous administration. The drug was detected up to 8 h of dosing in plasma of healthy and endometritic cows and the drug disposition followed three-compartment open model. The values of Vd(area), AUC, t(1/2beta), Cl(B), MRT and P/C ratio were 0.50 +/- 0.19 L.kg(-1), 62.2 +/- 23.3 microg.ml(-1).h, 1.02 +/- 0.07 h, 0.30 +/- 0.09 L.kg(-1).h(-1), 1.55 +/- 0.25 h and 0.52 +/- 0.27, respectively, in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Similarly, greater secretion of ceftriaxone into milk was also detected in cows with endometritis after IV administration, compared with results for control cows. 51 Finally, use of a population pharmacokinetic model revealed the need for a longer withdrawal interval than the FDAapproved withdrawal time 52 for flunixin in meat, which suggested a need for pharmacokinetic studies in both healthy and diseased animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, greater secretion of ceftriaxone into milk was also detected in cows with endometritis after IV administration, compared with results for control cows. 51 Finally, use of a population pharmacokinetic model revealed the need for a longer withdrawal interval than the FDAapproved withdrawal time 52 for flunixin in meat, which suggested a need for pharmacokinetic studies in both healthy and diseased animals.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, drug concentrations in milk derived from high-production quarters were significantly lower and depletion was more rapid than those from low-production quarters. Conversely, Kumar et al (2010) reported that ceftriaxone levels were lower and that CL was higher in diseased versus healthy cattle. A statistical analysis was not conducted to support this conclusion.…”
Section: Impact Of Disease As a Function Of Drug Classmentioning
confidence: 97%
“…Cephalosporin drug concentrations in milk were measured in two studies: intravenous ceftriaxone administered to healthy and diseased (endometritis) cows (Kumar et al, 2010) and intramammary infusion of ceftiofur hydrochloride to healthy and mastitic cattle (Han et al, 2017). Han's group did not observe any significant differences in either the milk or serum total ceftiofur concentrations as a function of infection.…”
Section: Impact Of Disease As a Function Of Drug Classmentioning
confidence: 99%
“…Pharmacokinetics of lincomycin has been conducted in dairy cattle (Weber et al1981), calves (Burrows et al 1983(Burrows et al , 1986, buffalo calves (Gouri et al 2014), pigs (Chaleva and Nquyen 1987;Nielsen and Gyrd-Hansen 1998), cats (Albarellos et al 2012(Albarellos et al , 2013 and chickens (El-Sayed et al 2015). Further, disease conditions are known to alter the disposition of antimicrobials (Kumar et al 2010;Burrows 1986). Fever is most common manifestations of infectious diseases and is reported to induce biochemical and physiological alterations in the cells (Van Miert 1987).…”
Section: Introductionmentioning
confidence: 99%